Teaching experience in the social media manager course in a situation of confinement by covid-19 - del Castillo, Ángel (Journal of Management and Business Education, 2021)
In the year 2020 we live the irruption of an unknown virus that caused our life habits to change. The various means through which a consumer can connect to the Internet took on greater importance, increasing the daily use of smartphones and personal computers. E-learning or virtual teaching became the only option to continue training from home. The strict confinement that was established, due to COVID-19, closed all the centers considered non-essential, such as schools, institutes or universities. The increase in students in this type of education in recent years was already a fact, since one of the main problems of traditional education, geographic distance, was eliminated. The objective of the research is based on demonstrating, through experience in the Social Media Manager course, that in the face of the COVID-19 situation, online training, e-learning or virtual teaching facilitated the ability to continue training at people from home and that a high percentage completed the course satisfactorily. For this, we present the theoretical framework where e-learning is located, as well as the experience in virtual teaching in the Continuing Training Course "Social Media Manager", which was taught entirely online through the Virtual Classroom of the university in a situation of total confinement due to the COVID-19 virus. And although some studies indicate that there is low motivation and a high degree of abandonment in this type of study, in our case the results show that 82.5% did it satisfactorily with an “Apt” grade, and only there was one student (2.5%) who did not get to carry out any activity of the course. Research shows us that with optimal resources and good management, positive results can be achieved.